1998
DOI: 10.1111/j.1469-7793.1998.073bx.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a hyperpolarization‐activated current in dedifferentiated adult rat ventricular cells in primary culture

Abstract: The presence of a hyperpolarization‐activated pacemaker (If)‐like current was tested in dedifferentiated adult rat ventricular myocytes up to 12 days in primary culture with the whole‐cell patch clamp technique. An If‐like current was found and characterized on freshly isolated and cultured ventricular cells. Both activation and density of the current varied in relation to the stage of dedifferentiation. The current was activated from ‐92.0 ± 2.5 and ‐63.0 ± 1.0 mV at the beginning (4‐day‐cultured cells) and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
46
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 48 publications
(55 citation statements)
references
References 36 publications
9
46
0
Order By: Relevance
“…increased in atrial myocytes isolated from adult rats with growth hormone-secreting tumors, and Fares et al 8 reported that I Ca,T was observed in dedifferentiated adult ventricular myocytes cultured for 8 days with serum-containing media. Consistent with our previous reports, 12,13 in DS rats at the LVH stage, the LV tissue ET-1 peptide level was within normal limits, contrasting with the abrupt and massive increase at the CHF stage.…”
Section: Izumi Et Al Et-1 Induces I Cat In Ventricular Myocytes 2533mentioning
confidence: 99%
See 2 more Smart Citations
“…increased in atrial myocytes isolated from adult rats with growth hormone-secreting tumors, and Fares et al 8 reported that I Ca,T was observed in dedifferentiated adult ventricular myocytes cultured for 8 days with serum-containing media. Consistent with our previous reports, 12,13 in DS rats at the LVH stage, the LV tissue ET-1 peptide level was within normal limits, contrasting with the abrupt and massive increase at the CHF stage.…”
Section: Izumi Et Al Et-1 Induces I Cat In Ventricular Myocytes 2533mentioning
confidence: 99%
“…14 Adult ventricular myocytes were isolated from 11-to 13-week-old male Sprague-Dawley rats (nϭ7), purified (Ͼ98%), and primarycultured in laminin-coated dishes, following the protocol used by Piper et al 15,16 and Fares et al 8 …”
Section: Isolation and Primary Culture Of Adult Rat Ventricular Myocytesmentioning
confidence: 99%
See 1 more Smart Citation
“…Because a previous report indicated that longer culture conditions resulted in a marked positive shift in activation of native current, 9 we first compared native I f between acutely dissociated cells and cells maintained in serum-free medium for 2 days. All cells studied were rod-shaped and quiescent.…”
Section: Comparison Of Neonatal and Adult Ventricular Myocytes Expresmentioning
confidence: 99%
“…However, I f is present in both automatic 1 and nonautomatic [2][3][4][5][6] regions of the heart, and the threshold voltage varies widely among cardiac regions, being least negative in sinus node (Ϫ40 mV in rabbit 7 ) and most negative in ventricle (Ϫ108 mV or more negative 5,8,9 ). Interestingly, I f activates at less negative voltages in newborn ventricle (Ϫ70 mV in rat 8,10 ).…”
mentioning
confidence: 99%